Conditionality as Targeting? Participation and Distributional Effects of Conditional Cash Transfers - Rodriguez-Castelan, Carlos (World Bank E-Library Archive, 2017)
Conditional cash transfer programs, whereby transfers to households are conditional on school attendance or health checkups, have become a widespread policy tool. They are viewed as a means of immediate poverty alleviation through the cash payments, and as a foundation of long-term poverty reduction through the emphasis on human capital formation. Because targeted transfers are usually conditioned on the consumption of normal goods, richer eligible households are more likely to consume more educational and health care opportunities than poorer ones. Thus, the eligible poorest households may benefit least from conditional cash transfers even to the extent that they may not participate at all. If conditionality is conceptualized as a cost at the margin, it may be leading poor households to opt out. This paper proposes a framework to model household decision making on participation (or not) in cash transfer programs depending on whether a conditionality exists. The paper outlines the optimal size of the cash transfer such that a fixed government budget maximizes the poverty reduction. The paper also shows that unconditional cash transfers may be preferable over conditional cash transfers if a government has a sufficiently high degree of poverty aversion, that is, if, beyond the poverty headcount, the government cares about how poor the poor are or the distance of the poorest among the poor below the poverty line. This basic argument carries over from income poverty to education poverty. The framework can be useful in shaping the recent discussion on the merits of universal benefits over conditional transfers in reducing poverty